Estudo da sustentabilidade na geração de energia elétrica por usina termelétrica a carvão mineral - Matias, Hernani Tabarelli (2017)
Brazil's energy and electrical matrix is one of the cleanest and most renewable in the world. Its planning and expansion considers factors such as sector performance, economic and social development. Investments in infrastructure that are aligned with the country's development policies as well as the sustainable development of the energy sector are needed. The Mines and Energy’ Ministry foresees significant participation of renewable sources in the energy matrix, but a country's energy system, particularly electric power, must rely on several sources of primary energy for maintenance and stability of the available energy in the transmission networks, because renewable sources are subject to weather and seasonality. Thus, fossil sources such as coal are used in thermoelectric plants and there is a forecast of an increase in the supply of electric energy by this source until the year 2030. This type of energy generation has as main disadvantage the pollution and environmental impact resulting from exploitation, processing and combustion of coal, such as greenhouse gas emissions, fly and bottom ashes, acidification of water resources, among others, due to the quality of the national mineral coal. In this context, the objective of this work is to study the aspects related to sustainability in the generation of electric energy by coal combustion through a unique case study of the Thermoelectric Complex located in south region of Brazil. The choice is justified because it is the largest thermoelectric complex in installed capacity in Brazil. This study has an exploratory and qualitative approach. Documents of the energy sector and environment, reports of the object of study, semi-structured interview with environment worker and a technical visit complete the sources of evidence used in this study that were analyzed the contents and triangulated. The main results of the research are the impacts on the environment, such as groundwater contamination and atmospheric emissions, ash generation and management. Among the benefits found are the development of local companies and suppliers, employment generation and technical and scientific knowledge. It is concluded that a well-structured environmental management system is an important tool so that the pros and cons of this form of electric power generation are communicated and mitigated, besides evidencing the importance of this enterprise for the regional development, since it is an important mover of the local economy.